Fashion elements in Kdrama female characters that influence Filipino women empowerment - Lanza, Zofia Louise Nichole P. (College of Home Economics, University of the Philippines Diliman, 2023)
Over the years, watching Kdrama has become a pastime for many Filipino viewers. This became more evident during the peak of the COVID-19 pandemic from 2020 to 2021. Filipinos began appreciating Korean pop culture as a whole and its components primarily because of its refreshing, forward-looking and constantly evolving themes (Nonato, 2020). Women, especially, are drawn to these shows not only because of the plot but also because of the female characters usually depicted as empowered women. This descriptive research study examines the fashion elements as seen in the clothing of female characters in Kdrama that may influence the perception of selected Filipinas with respect to women empowerment. It aims to analyze the different fashion elements such as texture, color, shape or silhouette, and lines, as worn by female characters in Kdramas and if they contribute to perceived Filipino women empowerment. To achieve the research objective, a two-part data collection process will be conducted. Phase 1 requires a survey of 100 Filipino women aged 16 to 30 years who are currently residing in the National Capital Region. Phase 2 requires a focus group discussion (FGD) with 30 participants, divided into five groups of six, selected from 100 participants from Phase 1. The data gathered from the FGD will help obtain further information from the participants by allowing them to fully explain and elaborate their answers to the initial survey questions. From there, the specific fashion elements which help influence the perception of the participants of women empowerment will be determined.